The Practical Study of Sinewave Inverters And modified Sinewave Inverters (Damascus University Journal for engineering sciences, 2021)
The power industry has been evolving towards cleaner and more abundant sources of energy. Renewable energy is becoming mainstream studies in the power generation. Nowadays we have become more and more reliant on electrical and electronic appliances. Appliances such as TVs, mobile phones, microwave ovens, lights, heaters, fans and more, are built around the AC mains supply from the public grid.With the advance of the renewable energy sources off grid power has become within affordable reach and many consumers have invested in such technologies, such as Solar panels and wind power generators. Both technologies have peak time and down time thus to allow for continuous power availability throughout the day, batteries are used to store the electrical energy generated by the source and then electronic devices such as inverters are used to generate mains level voltages to allow the appliances to work with the off grid system. This study will cover the two main solutions that are commonly used, the Pure Sinewave Inverter and the Modified Sinewave Inverter covering the advantages and disadvantages for each type from a consumer perspective.
Keywords: Sinewave Inverter; Modified Sinewave Inverter; Harmonics; Renewable Energy